AKTIVITAS ANTIJAMUR SENYAWA BIOAKTIF EKSTRAK Gelidium latifolium TERHADAP Candida albicans - Lutfiyanti, Rosiska; Ma'ruf, Widodo Farid; Dewi, Eko Nurcahya (Jurusan Perikanan, Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2012)
Abstract Gelidium sp. has bioactive compounds which is estimated has potential activity as antifungal. The aim of this study were to know bioactive compounds from Gelidium latifolium with different solvent, to know the potency of Gelidium latifolium extract as antifungal towards C. albicans and to know the effect of different concentration of Gelidium latifolium extract towards antifungal activity. The result showed that the methanol extract is able to produce inhibition zones toward Candida albicans, whereas n-hexane extract and acetone extract could not produce the inhibition zones. The highest inhibition zone was found at concentration of 12 mg/ml, that is 8 mm. The result of phytochemical screening test indicates that there were alkaloid, triterpenoids, and steroid in methanol extract. Gelidium latifolium is considered as potential source of natural antifungal agent, the antifungal agent was polar compound Â